Proceedings of the Second International Symposium on Parallel Symbolic Computation - PASCO '97 1997
DOI: 10.1145/266670.266680
|View full text |Cite
|
Sign up to set email alerts
|

Towards an efficient implementation of a fast algorithm for multipoint polynomial evaluation and its parallel processing

Abstract: The problem of multipoint polynomial evaluation is revisited znd a new improved algorithm ia presented. The fastness of the algorithm heavily depends on the use of the DFT-based algorithm for polynomial multiplication, and its detailed de scription and analysis are pr-ented in order for an efficient implementation and for efficient task scheduling in parallel processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These timings are also available in the form of plots with Figures 1 and 2 where radix-2 logscales are used on both axes. We found that our implementation does not perform well until degree 2 15 . In degree 2…”
Section: Propositionmentioning
confidence: 82%
See 1 more Smart Citation
“…These timings are also available in the form of plots with Figures 1 and 2 where radix-2 logscales are used on both axes. We found that our implementation does not perform well until degree 2 15 . In degree 2…”
Section: Propositionmentioning
confidence: 82%
“…The span and parallelism overhead of our algorithm are measured considering the many-core machine model of [8]. The paper [15] briefly discusses the parallelization of FFT-based multi-point evaluation without considering parallelism overhead, adaptive algorithms nor reporting on an implementation.…”
Section: Introductionmentioning
confidence: 99%